Bohdan Ilyich Simenach - "ORTHOPAEDICS, TRAUMATOLOGY AND PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On October 7, 2020, at the age of 100, life ceased to beat the heart of an outstanding scientist, a wonderful man, laureate of the State Prize of Ukraine, doctor of medicalSciences of Professor Bohdan Ilyich Simenach.